Profile of Road Traffic Accidents & Head Injury in Jaipur (Rajasthan) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
The injuries and death due to road traffic accidents are inescapable in the modern way of life and their correct interpretation is vital to the reconstruction of the events of Forensic Medicine and their proper management for treatment of the injured. The present study was conducted in the department of forensic medicine, SMS medical college, Jaipur in year 2003-2004 to analyze the quantity of the magnitude of death due to Road Traffic Accidents (RTA s) and to provide epidemiological data, so the preventive measures can be undertaken. The study shows that majority of the victims of RTA s were male of middle age group (20-40 years) when they were going on two wheelers with out wearing helmets.
Keywords: Road Traffic Accident (RTA); Head injury; Intra-cranial